CGIAR climate security team pilots a new research approach for the development of nature-based solutions in fragile settings - Schapendonk, Frans; Caroli, Giulia (2025)
Responding to complex crises requires new systemic research approaches that help identify entry points for programmes that can simultaneously address risks of different nature while building long-term resilience of affected populations. Under CGIAR’s Food Frontiers and Security (FFS) and Climate Action Science Programmes (CASP), CGIAR’s Climate Security team has piloted a new research approach in Cabo Delgado, Northern Mozambique, combining ecosystem-based assessment with participatory conflict analysis. Commissioned by the United Nations World Food Programme (WFP), the study allows for the targeted development of Nature-based Solutions (NbS) in fragile settings.